2009
DOI: 10.1039/b823173g
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-dot-coated encoded silica colloidal crystals beads for multiplex coding

Abstract: Multiplex optical coding carriers for biological assays have been achieved by coating silica colloidal crystals beads with quantum dots, which provided high stability, large capacity and simplicity for practical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Han et al were the first to apply QD-tagged 1.2 µm polymer microspheres to the multiplexed optical coding of DNA hybridization (Han et al, 2001). Fuelled by their studies, the following three preparation methods for optical QD-encoded microspheres were developed: (i) incorporation of QDs during microsphere synthesis (Joumaa et al, 2006;Li et al, 2005;Vaidya et al, 2007;Wang and Seo, 2008;Yang et al, 2006), (ii) deposition of QDs onto bead surfaces through layer-bylayer adsorption (Li et al, 2009a(Li et al, , 2009bRauf et al, 2009), and (iii) diffusion of hydrophobic QDs into polymeric microspheres. Encoded microspheres are usually prepared by embedding hydrophobic microspheres with hydrophobic QDs via porosity partitioning and entrapment or swelling (Bradley et al, 2005;Gao and Nie, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Han et al were the first to apply QD-tagged 1.2 µm polymer microspheres to the multiplexed optical coding of DNA hybridization (Han et al, 2001). Fuelled by their studies, the following three preparation methods for optical QD-encoded microspheres were developed: (i) incorporation of QDs during microsphere synthesis (Joumaa et al, 2006;Li et al, 2005;Vaidya et al, 2007;Wang and Seo, 2008;Yang et al, 2006), (ii) deposition of QDs onto bead surfaces through layer-bylayer adsorption (Li et al, 2009a(Li et al, , 2009bRauf et al, 2009), and (iii) diffusion of hydrophobic QDs into polymeric microspheres. Encoded microspheres are usually prepared by embedding hydrophobic microspheres with hydrophobic QDs via porosity partitioning and entrapment or swelling (Bradley et al, 2005;Gao and Nie, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Wilson et al described a simple method for preparing encoded microspheres by assembling hydrophobic CdSe/ZnS quantum dots on polyamine-coated microspheres in chloroform [8]. Li and Sukhanova et al showed the possibility to obtain hundreds of codes by depositing differentwavelength QDs on surfaces of silica colloidal crystals beads, and demonstrated the application of the nanocrystal-encoded microbeads for DNA assay and proteomics [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…To increase the encoding capacity of the PCBs, semiconductor QDs with different colors and intensities could also be integrated into the PCBs to achieve joint encoding. [95][96][97] Despite its many advantages, the evaporation rate of the approach for PCB generation is usually slow as it takes several hours at room temperature for complete consolidation. [ 98 ] Thus, a major obstacle to the generation of the PCBs in bulk is the lack of simple and reliable methods for consolidating the colloidal particles into crystals in fast time scales.…”
Section: Phc Barcodes From Single Emulsionsmentioning
confidence: 99%